2015
DOI: 10.1155/2015/573814
|View full text |Cite
|
Sign up to set email alerts
|

Serrated Polyps and Their Alternative Pathway to the Colorectal Cancer: A Systematic Review

Abstract: Colorectal cancer (CRC) is the third most frequently diagnosed cancer in the world. For a long time, only one pathway of colorectal carcinogenesis was known. In recent years, a new “alternative” pathway through serrated adenoma was described. Recent meta-analysis estimated these cancers as about 10% to 30% of all CRCs. Serrated polyps are the second most popular groups of polyps (after conventional adenomas) found during colonoscopy. Serrated polyps of the colon are clinically and molecularly diverse changes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 61 publications
0
30
0
3
Order By: Relevance
“…SSA/Ps are considered the precursor lesion for many sporadic CRCs with microsatellite instability and for other CRCs characterized by hypermethylation (2527). Initially, we evaluated TSAs and SSA/Ps as separate groups, given a presumed distinct etiology (28). While we did not identify significant differences in miRs between TSAs and HGTVs, there were several differentially expressed miRs observed between HPNMs and TSAs.…”
Section: Resultsmentioning
confidence: 99%
“…SSA/Ps are considered the precursor lesion for many sporadic CRCs with microsatellite instability and for other CRCs characterized by hypermethylation (2527). Initially, we evaluated TSAs and SSA/Ps as separate groups, given a presumed distinct etiology (28). While we did not identify significant differences in miRs between TSAs and HGTVs, there were several differentially expressed miRs observed between HPNMs and TSAs.…”
Section: Resultsmentioning
confidence: 99%
“…First, sporadic colorectal carcinogenesis has a diversity of pathogeneses and pathways (25)(26)(27); on the other hand, the primary and main pathogenesis of colitic cancer is chronic mucosal inflammation. Moreover, this pathogenic inflammation is diffusely distributed in the colon, which means that examining this non-neoplastic mucosa could give indications of the accumulated genetic change in UC-associated carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent published evidence, however, has indicated that there are three distinct sub-categories of SP, most commonly classified as hyperplastic polyps (HP), sessile serrated adenomas/polyps (SSA/P) and traditional serrated adenomas (TSA) 10 . SSA/P and TSA are now understood to harbour malignant potential 11 .…”
Section: Introductionmentioning
confidence: 99%